What’s beyond the core? Database coverage in qualitative information reveal - Jennifer Horton; David Kaunelis; Danielle Rabb; Andrea Smith (Journal of the Medical Library Association)
Objective: This study investigates the effectiveness of bibliographic databases to retrieve qualitative studies for use in systematic and rapid reviews in Health Technology Assessment (HTA) research. Qualitative research is becoming more prevalent in reviews and health technology assessment, but standardized search methodologies—particularly regarding database selection—are still in development.